The Consumption Pattern in Islamic Perspective Between Needs, Desires, and Ethics - Mallika, Raiza Pujia; Agustin, Xena Angelica; Kholmi, Masiyah (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to explore consumption patterns from the perspective of Islam, focusing on the distinction between needs and desires as well as the implementation of ethical consumption in daily life. Islam teaches its followers to maintain a balanced consumption pattern, where the fulfillment of basic needs is prioritized and excessive desires are controlled. This study uses a descriptive qualitative approach with library research as the main method to identify the fundamental principles of consumption in Islam, including the concepts of halal, thayyib, and wasathiyah. The findings indicate that consumption in Islam is not only determined by physical needs but also by ethical principles that prioritize individual and societal well-being. Furthermore, the challenges of globalization and the rising consumer culture in modern society can lead to consumption patterns that contradict Islamic teachings. Therefore, the application of Islamic consumption principles is crucial in addressing the phenomenon of excessive and uncontrolled consumption in today's modern era. Keywords: Consumption, Islam, Needs, Desires REFERENCES Chapra, M. U. (2000). The future of economics: An Islamic perspective. The Islamic Foundation. Dusuki, A. W., & Abozaid, A. (2007). A critical appraisal on the challenges of realizing Maqasid al-Shari’ah in Islamic banking and finance. International Journal of Economics, Management and Accounting, 15(2), 143-165. Haneef, M. A. (2005). A critical survey of Islamization of knowledge. International Institute of Islamic Thought. Hasan, Z. (2009). Islamic consumer behavior: A conceptual framework. Journal of Islamic Economics, Banking and Finance, 5(1), 1–25. Ritzer, G. (2011). The McDonaldization of society (6th ed.). SAGE Publications. Zed, M. (2004). Library research methods. Jakarta: Yayasan Obor Indonesia. Patton, M. Q. (2002). Qualitative research & evaluation methods (3rd ed.). SAGE Publications. Braun, V., & Clarke, V. (2006). Using thematic analysis in psychology. Qualitative Research in Psychology, 3(2), 77–101. Amiruddin, A. (2019). Consumption ethics in the Islamic perspective. Jakarta: Kencana. Yusanto, M., & Widjajakusuma, A. (2002). Islamic economics: Solutions for the economic problems of the ummah. Jakarta: Gema Insani Press. Fatah, A. (2015). Consumption patterns from the Islamic economic perspective. Journal of Islamic Economics, Theory and Practice, 2(9), 731–743. https://doi.org/10.20473/vol2iss20159pp731-743 Sari, D. K. (2018). Halal consumption in the Islamic perspective and its implications on Muslim consumer behavior. Journal of Islamic Economics and Business, 3(2), 89–101. Mubarok, A. (2017). Consumerism in the Islamic view: A study of the consumerist lifestyle in modern society. Journal of Islamic Economics, 3(01), 55–64.